Phase matching between energy-time entanglement and two photon absorption processes - Hofmann, Holger F; Li, Baihong (SPIE, 2021)
Energy-time entanglement can enhance two photon absorption by combining a precise two photon resonance with temporal correlations between the arrival times of the two photons. In general, the optimal timing of photon arrival is determined by the dynamics of the system between the initial and the final excitations. In this presentation, we show that the optimal timing of photon arrival corresponds to a specific phase dispersion in the frequency difference of the two photons. The absorption cross-section of energy-time entangled photons can be enhanced beyond the rate observed for optimal photon coincidence by adjusting the phase dispersion of one of the photons to match the optimal characteristics. We determine the maximal enhancement factor as a function of the bandwidth of the intermediate states and their detuning relative to the average photon frequency. Significant additional enhancements can be achieved when the bandwidth of the intermediate states is very narrow.